Analisis Kelayakan Investasi Asphalt Mixing Plant (Studi Kasus: PT Perwita Karya di Base Camp Piyungan, Bantul) - Mandiyo Priyo; Aditya Gunawan (Semesta Teknika, 2009)
The construction sector has contributed an important role in the development, especially in Yogyakarta Special Region. To implement this role, the construction sector is in front of the challenge to present the excellent quality of their construction works. This condition is able to initiate the opportunities for private industries to invest in this sector whether it is expansion or diversification. As similar with other investment projects, financial feasibility analysis in civil construction sector is becoming a main consideration in the investment plan. This paper presents the application of financial feasibility analysis on the development plan of the asphalt mixing plant. Financial analyses used in this study were Rate of Return on Investment (TPI), Return on Equity (TPMS), Break Event Point (BEP) and Net Present Value (NPV). A case study of Asphalt Mixing Plant investment plan owned by PT. Perwita Works which is located in Piyungan District, Bantul, Yogyakarta was considered in this study. From the results, it shows that TPMS value of AMP investment plan was found to be 3.575 which indicate that the investment is profitable. Break Event Point (BEP) in year of 1992 reached over 8 months with the total revenue and NPV value of IDR 6,190,445,178.00 and IDR 7,144,013,903.00, respectively. It means that the investment can be paid back and the company receives the profit of IDR 7,144,013,903.00.